Intravoxel incoherent motion imaging in monitoring the function of kidney allograft. (July 2019) - Sulkowska, Katarzyna; Palczewski, Piotr; Wojcik, Damian; Ciszek, Michal; Sanko-Resmer, Joanna; Wojtowicz, Joanna; Leszkiewicz, Marek; Golebiowski, Marek
Background: Non-invasive alternatives to percutaneous renal biopsy are sought for follow-up of renal allografts. Purpose: To evaluate the feasibility of intravoxel incoherent motion (IVIM) imaging in monitoring and predicting the function of renal allografts. Material and Methods: Thirty-five kidney recipients were examined on a 1.5-T MR unit approximately three and 18 months after transplantation. Based on estimated glomerular filtration rate (eGFR), patients were divided into three groups: improved; declined; and stable graft function. Diffusion parameters were calculated with the use of monoexponential (total apparent diffusion coefficient [ADCT ]) and biexponential (pure diffusion coefficient [D], perfusion fraction [Fp]) model and compared among and within study groups using Kruskal–Wallis, Mann–Whitney, and Wilcoxon matched pairs tests. Diffusion parameters were correlated with eGFR using Spearman's rank correlation coefficients. Results of tests with P values < 0.05 were considered statistically significant. Results: Values of diffusion parameters, especially Fp, were lower in patients with a declined graft function; however, statistically significant intergroup differences were observed only in a limited number of parameters at the time of follow-up magnetic resonance imaging (MRI). None of the diffusion parameters from the baseline MRI correlated with the change in eGFR over time. Flow-related diffusion parameters calculated with the IVIM model showed high variability. Conclusion: We observed a trend toward a decrease in values of diffusion parameters in patients with a declined graft function. Further research is needed to verify a clinical usefulness of this observation.